2017
DOI: 10.1080/10717544.2016.1247928
|View full text |Cite
|
Sign up to set email alerts
|

Ocular ketoconazole-loaded proniosomal gels: formulation, ex vivo corneal permeation and in vivo studies

Abstract: Context: Vesicular drug carriers for ocular delivery have gained a real potential. Proniosomal gels as ocular drug carriers have been proven to be an effective way to improve bioavailability and patient compliance. Objective: Formulation and in vitro/ex vivo/in vivo characterization of ketoconazole (KET)-loaded proniosomal gels for the treatment of ocular keratitis. Materials and methods: The effect of formulation variables; HLB value, type and concentration of non-ionic surfactants (Tweens, Spans, Brijs and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 46 publications
2
51
1
Order By: Relevance
“…(3-5) showed the release profiles of from the prepared niosomes which were occurring in two distinct phases, an initial phase in which rapid drug leakage was observed and stayed for about 8 h, followed by slow phase continued for 16 h. The initial phase was due to desorption of the drug from the surface of niosomes while the drug release in the slow phase was regulated by diffusion through the swollen niosomal bilayers and breakage of polymers [17]. This was inconsistent with Abdelbary et al, [2017] who found that the release profiles of ketoconazole from the different prepared proniosomal gel formulae were found to be biphasic release, A rapid drug leakage was observed in the initial phase, where about 25-55 % of the entrapped drug was released within the first few hours, while in the second phase, a slow release of the drug was observed from the different proniosomal formulations [18]. But, this was not inconsistent with Kumar et al, [2017] who found that the release of Cefixime from niosomal suspension occurred slowly and later immediate release due to penetration enhancement of nonionic surfactant [19].…”
Section: Entrapment Efficiency Of Itraconazole Proniosomescontrasting
confidence: 53%
“…(3-5) showed the release profiles of from the prepared niosomes which were occurring in two distinct phases, an initial phase in which rapid drug leakage was observed and stayed for about 8 h, followed by slow phase continued for 16 h. The initial phase was due to desorption of the drug from the surface of niosomes while the drug release in the slow phase was regulated by diffusion through the swollen niosomal bilayers and breakage of polymers [17]. This was inconsistent with Abdelbary et al, [2017] who found that the release profiles of ketoconazole from the different prepared proniosomal gel formulae were found to be biphasic release, A rapid drug leakage was observed in the initial phase, where about 25-55 % of the entrapped drug was released within the first few hours, while in the second phase, a slow release of the drug was observed from the different proniosomal formulations [18]. But, this was not inconsistent with Kumar et al, [2017] who found that the release of Cefixime from niosomal suspension occurred slowly and later immediate release due to penetration enhancement of nonionic surfactant [19].…”
Section: Entrapment Efficiency Of Itraconazole Proniosomescontrasting
confidence: 53%
“…The cornea and conjunctiva have a negative charge where these mucoadhesive polymers may interact intimately with these extraocular structures [25], would increase the concentration and residence time of the associated drug. The elevated PSP levels in the cornea and aqueous humor following the administration of PSP-Gel might be due to the increase in the amount of PSP dissolved in the precorneal area leading to the high concentration gradient, favoring good permeation, together with higher contact time with the corneal area [63]. The results obtained show that all the formulations were found to contain almost same amount of drug after 6 mo.…”
Section: Pharmacokinetic Studymentioning
confidence: 85%
“…Proniosomal gel was prepared by incorporating various nonionic surfactants and maintained a ratio 1:1 w/w with lecithin along with a fixed amount (50 mg) of cholesterol. Ultimately sufficient amount of water incorporated into the formulation to enable swelling of bilayer resulting in efficient vesicular structures [50]. Significantly highest EE was acquired for a formula with span 65 and lecithin in 1:1 w/w ratio.…”
Section: Concise Evidence Of Published Proniosomal Gel Formulations Amentioning
confidence: 99%